Trends Composition and Amount of Municipal Solid Waste In Namdam Sub district, Tungyangdaeng District, Pattani Province - Kaewmanee, Juthamat (Journal of Science and Technology Songkhla Rajabhat University, 2021)
The research has the objective study trends, composition and amount of municipal solid waste in the area Nam Dam Subdistrict, Thung Yang Daeng District Pattani Province And to predict the amount of solid waste occurring in the future in the next 10 years of Nam Dam Subdistrict Thung Yang Daeng District Pattani Province The study was conducted in five villages from 12 solid waste collection points over a 2-month period from January to February 2020. The Results of solid waste in Nam Dam Subdistrict community Thung yangdaeng District Pattani province, by the result of the average amount of waste is 7,617.75 kg / month, which February is the largest amount of waste. Solid waste study results Most of them are components of plastic waste, the highest average is followed by food waste.The results of the 10 year waste forecasting of communities in Namdam Subdistrict, Tungyangdaeng District, Pattani Province, show that the amount of waste is likely to increase with increasing population and Buddhist years. According to the forecast of solid waste in the 10th year, the communities in Namdam Subdistrict, Tungyangdaeng District, Pattani Province Solid waste will occur up to 531.36 kg/day.